The association between late preterm birth and cardiometabolic conditions across the life course: A systematic review and meta‐analysis. Issue 2 (22nd November 2021) - Yoshida‐Montezuma, Yulika; Stone, Erica; Iftikhar, Saman; De Rubeis, Vanessa; Andreacchi, Alessandra T.; Keown‐Stoneman, Charles; Mbuagbaw, Lawrence; Brown, Hilary K.; de Souza, Russell J.; Anderson, Laura N.
Abstract: Background: The effect of being born late preterm (34–36 weeks gestation) on cardiometabolic outcomes across the life course is unclear. Objectives: To systematically review the association between being born late preterm (spontaneous or indicated), compared to the term and cardiometabolic outcomes in children and adults. Data sources: EMBASE(Ovid), MEDLINE(Ovid), CINAHL. Study selection and data extraction: Observational studies up to July 2021 were included. Study characteristics, gestational age, cardiometabolic outcomes, risk ratios (RRs), odds ratios (ORs), hazard ratios (HRs), mean differences and 95% confidence intervals (CIs) were extracted. Synthesis: We pooled converted RRs using random‐effects meta‐analyses for diabetes, hypertension, ischemic heart disease (IHD) and body mass index (BMI) with subgroups for children and adults. The risk of bias was assessed using the Newcastle‐Ottawa scale and certainty of the evidence was assessed using the grading of recommendations, assessment, development and evaluation (GRADE) approach. Results: Forty‐one studies were included (41, 203, 468 total participants; median: 5.0% late preterm). Late preterm birth was associated with increased diabetes (RR 1.24, 95% CI 1.17, 1.32; nine studies; n = 6, 056, 511; incidence 0.9%; I 2 51%; low certainty) and hypertension (RR 1.21, 95% CI 1.13, 1.30; 11 studies; n = 3, 983, 141; incidence 3.4%; I 2 64%; low certainty) in children and adults combined. Late preterm birth was associated with decreased BMI z ‐scores in children (standard mean difference −0.38; 95% CI −0.67, −0.09; five studies; n = 32, 602; proportion late preterm 8.3%; I 2 96%; very low certainty). There was insufficient evidence that late preterm birth was associated with increased IHD risk in adults (HR 1.20, 95% CI 0.89, 1.62; four studies; n = 2, 706, 806; incidence 0.3%; I 2 87%; very low certainty). Conclusions: Late preterm birth was associated with an increased risk of diabetes and hypertension. The certainty of the evidence was low or very low. Inconsistencies in late preterm and term definitions, confounding variables and outcome age limited the comparability of studies.